(untitled) (Praxis Educativa, 2012)
This paper discusses the implicit problems in assessment processes related to plans and programs that promote citizenship and coexistence in multicultural societies. Once identified some characteristics about the nature of the phenomenon under study, we establish three criteria to be considered in any theoretical and methodological approach on the subject, namely: a) the procedural and democratic character that should guide the design and implementation of any strategy evaluation that is to be conducted on this topic, b) the moral nature of the object to evaluate since this is essentially about social values and behaviours, and c) the main purpose that guides the implementation and evaluation of these programs: civic empowerment by citizens of democratic rights and obligations that guide their participation in public life. According to this we adopted an operational model of participatory and democratic evaluation (MODE) and insist on the role of the evaluator as a person engaged in the construction and development of a critical citizenry that promotes the empowerment of individuals and the development of a more fair and egalitarian society.